SIGN IN NDUNGNDUNGEN KARO - DINI RAHMAYANI; ELIA MASA GINTINGS; TIARNITA MARIA SARJANI SIREGAR (State University of Medan, 2021)
This study dealt with sign in Ndungndungen Karo. The objectives of the study were to investigate the sign types (icon, index and symbol) used in Ndungndungen nasehat & Adat by using Peirce’s theory. This study was conducted by using descriptive qualitative method. The data of this study were 32 Ndungndungen Orang Tua, consisted of 16 Ndungndungen Nasehat and 16 Ndungndungen Adat from the book entitled 375 Ndungndungen Karo by P.Angelo PK. Purba OFM Cap. For collecting data, this study used the method of literature study and interview. The findings showed that the total numbers of sign classification were 59. There were (46%) Icon, (15%) Index and (39%) symbol. The use of icon became the most dominant types of sign classification found in Ndungndungen Nasehat dan adat after the use of symbol and index. The meanings of sign types (icon, index and symbol) found in Ndungndungen Nasehat dan adat to show their politeness in talk and the messages, advices, or as a guidance to their life.